Estereoisômeros da epóxi-carvona com atividade anticonvulsivante: um estudo comparativo. - Salgado, Paula Regina Rodrigues (2016)
The epoxy-carvone (EC) is a monoterpene present in herbs with proven pharmacological activity in the CNS, including, antinociceptive and anticonvulsant. This substance has chiral centers that permit the generation of four stereoisomers, called (+)-cis-EC, (-)-cis-EC, (+)-trans-EC and (-)-trans-EC, whose comparative anticonvulsant effects have never been studied. This work aims to investigate in a comparative way the anticonvulsant activity of enantiomers of EC cited in experimental models of chemical and electrical induction of seizures in mice and quantifying pro-inflammatory cytokines and perform histopathological analysis of the treated animals. In the test of the seizures induced by pentylenetetrazol, all stereoisomers tested (300 mg/kg; ip) were effective in protecting seizures, increasing the latency for appearances thereof. Since the test of the seizures induced by pilocarpine, substances (+)-cis-EC, (+)-trans-EC and (-)-trans-EC were most prominent in the reduction of parameters related to the activation of cholinergic receptors, and increase the latency to onset of seizures. No significant results were obtained in the test of seizures induced by strychnine, suggesting that possibly these drugs do not act in glycine receptors. In the maximum atrial electroshock model, difference was evident in the effect of EC stereoisomers and despite all reduce the duration of significantly convulsions, substances (+)-trans-EC and (-)-trans-EC showed a reduction even more pronounced. In the kindling test, (+)-cis-EC and (-)-cis-EC reduced the average scores presented with a small but noticeable, especially (+)-cis-EC. The stereoisomer (+)-cis-EC decreased levels of proinflammatory cytokines IL-1β, IL-6 and TNFα in the kindling test, whereas comparatively (-)-cis-EC did not reduce the amount of IL -1β. Histopathological analysis showed greater hippocampal neuronal protection for those treated with (+)-cis-EC. The group treated with (-)-cis-CE exhibited inflammatory components in this tissue, which again lists (+)-cis-EC as a promising, compared. Thus, these results show that the EC stereoisomers has similar anticonvulsant potential, especially (+)-cis-EC, which interferes possibly potentiating inhibitory pathways or inhibiting excitatory pathways, in addition to changing levels of cytokines involved in epileptic condition and promote neuronal protection mechanisms that require further investigation.